Improved stability with intramedullary stem after anterior femoral notching in total knee arthroplasty - Completo, A.
Purpose It has been hypothesized that femoral notching in total knee arthroplasties weakens the cortex of the femur, which can predispose to femoral fractures in the postoperative period. Some authors suggest that patients who sustain inadvertent notching should have additional protection in the postoperative period, and consideration should be given to the use of prophylactic femoral stems. In this case, a question can be raised: Is the use of femoral stem in an anterior femoral notching an effective way to reduce the fracture risk? We hypothesized that for a larger notch, the use of a femoral stem does not decrease considerably the stress-riser at the notch edge, and the use of stem is not enough to reduce the risk of fracture. Methods In the present in vitro study, twelve synthetic femurs were selected and used for the experiments under two load scenarios. Femoral components with and without femoral stems were implanted in femurs with different notch sizes to predict experimentally the strain levels at the notch edge with the use of fiber Bragg gratings and at notch region with strain gauges. Results Despite the global strain reduction in stemmed condition, at the notch edge, the strain behavior was dissimilar for the different notch depths. For notch depths lower than 5 mm, the use of stem reduces the strain level at the notch edge to values below the intact femur condition, while for depths greater or equal to 5 mm, the strain levels at the notch edge were higher than the intact femur condition with values ranging from ?10 to ?189%. Conclusions The present study suggests the use of a prophylactic stem for notch depths greater than 5 mm. For notch depths below 5 mm, the fracture risk due to strain increase at the notch edge seems to be low in the stemless condition.